Hepatocyte Growth Factor Enhances Engraftment and Function of Nonhuman Primate Islets - Fiaschi-Taesch, Nathalie M. (American Diabetes Association, 2008)
OBJECTIVE—Adenoviral delivery of hepatocyte growth factor (HGF) to rodent islets improves islet graft survival and function, markedly reducing the number of islets required to achieve glucose control. Here, we asked whether these prior observations in rodent models extend to nonhuman primate (NHP) islets. RESEARCH DESIGN AND METHODS—NHP islets were transduced with murine (Ad.mHGF) or human (Ad.hHGF) adenoviral HGF (Ad.HGF) at low multiplicity of infection and studied in vitro. To study the function of Ad.HGF-transduced NHP islets in vivo, a renal subcapsular marginal mass islet transplant model was developed in streptozotocin-induced diabetic NOD-SCID mice. RESULTS—Baseline glucose values were 454.7 ± 11.3 mg/dl (n = 7). Transplant of 500 NHP islet equivalents (IE) had only a marginal effect on blood glucose (369.1 ± 9.7 mg/dl, n = 5). In striking contrast, 500 NHP IE transduced with Ad.mHGF promptly and continuously corrected blood glucose (142.0 ± 6.2 mg/dl, n = 7) for the 6-week duration of the experiment. Unilateral nephrectomy resulted in an immediate return of glucose to baseline diabetic levels. Interestingly, adenoviral DNA, as well as mouse HGF (mHGF) mRNA derived from the adenovirus, were present for 42 days posttransplantation. Surprisingly, transplant of 500 IE with Ad.hHGF, as compared with Ad.mHGF, resulted in only marginal correction of blood glucose, suggesting that human HGF is less efficient than mHGF in this system. CONCLUSIONS—These studies demonstrate that mHGF markedly improves islet transplant outcomes in the highest preclinical species examined to date. HGF has promise as an agent that can improve islet mass and function in transplant models and likely in other models of types 1 and 2 diabetes.